Rationalization of Rainfall Station Density in the Jatiroto Sub-Watershed Using Ground and Satellite Rainfall Data - Megantara, Anggit Gilang; Wahyuni, Sri; Limantara, Lily Montarcih (Fakultas Teknik Universitas Brawijaya, 2022)
This study uses ground and CHIRPS data to rationalize the density of rainfall stations in the Jatiroto Sub-watershed, Lumajang Regency. This study aimed to determine the suitability of the CHIRPS satellite rainfall data to the measurement data. In addition, it determines the density of rainfall stations based on WMO standards. Also, the Kagan-Rodda method uses measurement and satellite data to determine rainfall station recommendations' results. The method used for the suitability test uses the value of RMSE, NSE, Correlation Coefficient, and Relative Error. And the WMO standard for analyzing the number of rainfall station. Knowing the rationalization and recommendations for placing rainfall stations using the Kagan-Rodda method by considering WMO standards, root mean square error, and interpolation errors. The results obtained include the appropriateness of satellite data, the number of rainfall stations at the research location according to WMO standards, and recommendations for rainfall stations based on Kagan-Rodda.